Pemanfaatan Kompos Ela Sagu, Sekam Dan Dedak Sebagai Media Perbanyakan Agens Hayati Trichoderma harzianum Rifai. - Costanza Uruilal; A. Marthin Kalay; Elizabet Kaya; Adelina Siregar (Faculty of Agriculture, Pattimura University, 2012)
The use of biological agents to prevent the growth of plant diseases is aimed at decreasing the capability of particular pathogen, preventing their growth and spread, reducing the infection and intensity of pathogenic attack to main plants. Trichoderma harzianum is commonly found in almost all types of soil, and is one of fungi that can be used as biological agents to control plant pathogens. Growth and development of this fungi are mostly influenced by factors such as temperature, light, air, and pH. It is also dependents on other nutrients such as carbon, nitrogen and plain carbohydrate which are contained in sago waste (ela), bran and rice husk. The objective of this study is to find out the utilization of sago waste, bran and rice husk as media to multiply the biological agents T. harzianum. The result of this study showed that sago waste compost could be used as a medium to multiply the antagonist T. harzianum; when appropriately mixed with bran and rice husk (1:1:1 v/v), sago waste composts would be an effective media to develop the T. harzianum fungus. This mixture is better compared to sago waste composts, husk, sago waste composts and bran, and sago waste composts and husk. It is doe to the fact that in the media number of spore of T. harzianum (7,08 x 109/mL) increased and colony characteristics was dense..